Efficacy of Bosutinib therapy as a second line in the treatment of chronic myeloid leukemia: A single-center study - Alaa Fadhil Alwan; Mushtaq M. Khazeem; Zaidoon Jamal Tuama (Iraqi Journal of Hematology)
BACKGROUND: Chronic myeloid leukemia (CML), a myeloproliferative neoplasm caused by genetic abnormality resulted in BCR-ABL1 fusion gene, leading to constitutive tyrosine kinase activity. Despite improved treatment outcomes of tyrosine kinase inhibitors (TKIs), resistance to these agents due to mutations in targeted BCR-ABL gene is still a challenge. Bosutinib is consider one of TKI, it inhibit both Sarcoma kinase and Ablson kinase (SRC/ABL), It is approved for patients for whom frontline TKIs is failed or undergo adverse effects. OBJECTIVE: This study aims to evaluate the efficacy of bosutinib as a second-line treatment for CML patients who have previously failed or experienced intolerance to other TKIs. MATERIALS AND METHODS: A cross-sectional study was conducted from October 2021 to December 2023 at the National Center of Hematology. Thirty CML patients were enrolled, all of whom had received bosutinib following failure or intolerance to prior TKI treatments (imatinib and/or nilotinib). Data collected included patient demographics, prior treatment history, and laboratory results. BCR-ABL levels were quantitatively measured using polymerase chain reaction at baseline and 6 months posttreatment. Statistical analyses included paired t-tests and correlation assessments. RESULTS: The study included 30 CML patients (12 males and 18 females) with a median age of 49.5 years. Most patients (60%) had received imatinib only prior to bosutinib. A significant decrease in mean BCR-ABL levels was observed after 6 months of bosutinib treatment (P < 0.0001), with 53% of patients achieving optimal molecular response as per the European LeukemiaNet criteria. Correlation analyses indicated significant relationships between BCR-ABL level and white blood cell count (P = 0.006) and between treatment duration and hemoglobin level (P = 0.001). In addition, patients previously treated solely with imatinib responded to bosutinib significantly better than those who had received both imatinib and nilotinib (P = 0.0272). CONCLUSION: Bosutinib demonstrated significant efficacy as a second-line treatment for CML in patients who showed failure response to prior TKI therapies. These findings support bosutinib usage in managing CML, particularly in patients with a history of single TKI treatment, and underscore the necessity for ongoing research into resistance mechanisms and alternative therapies.